Finding Antitubercular Leads from Marine-Derived and Entomopathogenic Fung - Suryani, Ni Luh Putu Indah; Putra, I Putu Yogi Astara; Ujam, Nonye Treasure; Ariantari, Ni Putu (Jurnal Farmasi Udayana; Vol. 12, No 1, Tahun 2023DO - 10.24843/JFU.2023.v12.i01.p09, 2023)
The occurrence of Mycobacterium tuberculosis resistance encourages the discovery of new antitubercular candidates. Microbes including fungi and bacteria are well known reservoir for isolating antibiotic compounds, among natural product resources. In this review, we report promising antitubercular compounds from marine-derived and entomopathogenic fungi, reported from 2000 to 2022. A comprehensive literature search was conducted through scientific websites, including Google Scholar, Springer, and Pubmed. Eighty-three antitubercular compounds were reported, where 57 of them derived from fungi associated with marine ecosystem. Those fungi belong to 10 fungal genera. The remaining active compounds were isolated from 7 genera of entomopathogenic fungi. Gliotoxin, 12,13-dihydroxy-fumitremorgin, and helvolic acid as well as hirsutellones A-D are among bioactive compounds reported for their remarkable antitubercular activity, which promising to be investigated further in the search of antitubercular leads. Deeper investigation on these compounds might be promising for the the discovery of antitubercular candidates in the future. Keywords: Antitubercular; entomopathogenic fungi; marine-derived fungi; Mycobaterium tuberculosis ; secondary metabolites